Intestinal epithelial cell-derived IL-15 determines local maintenance and maturation of intra-epithelial lymphocytes in the intestine. (26th December 2019) - Zhu, Yuanbo; Cui, Guangwei; Miyauchi, Eiji; Nakanishi, Yuki; Mukohira, Hisa; Shimba, Akihiro; Abe, Shinya; Tani-ichi, Shizue; Hara, Takahiro; Nakase, Hiroshi; Chiba, Tsutomu; Sehara-Fujisawa, Atsuko; et al.
Abstract : IL-15 is essential for intraepithelial lymphocyte homeostasis Abstract: Abstract Interleukin-15 (IL-15) is a cytokine critical for maintenance of intestinal intra-epithelial lymphocytes (IELs), especially CD8αα  + IELs (CD8αα IELs). In the intestine, IL-15 is produced by intestinal epithelial cells (IECs), blood vascular endothelial cells (BECs) and hematopoietic cells. However, the precise role of intestinal IL-15 on IELs is still unknown. To address the question, we generated two kinds of IL-15 conditional knockout (IL-15cKO) mice: villin-Cre (Vil-Cre) and Tie2-Cre IL-15cKO mice. IEC-derived IL-15 was specifically deleted in Vil-Cre IL-15cKO mice, whereas IL-15 produced by BECs and hematopoietic cells was deleted in Tie2-Cre IL-15cKO mice. The cell number and frequency of CD8αα IELs and NK IELs were significantly reduced in Vil-Cre IL-15cKO mice. By contrast, CD8αα IELs were unchanged in Tie2-Cre IL-15cKO mice, indicating that IL-15 produced by BECs and hematopoietic cells is dispensable for CD8αα IELs. Expression of an anti-apoptotic factor, Bcl-2, was decreased, whereas Fas expression was increased in CD8αα IELs of Vil-Cre IL-15cKO mice. Forced expression of Bcl-2 by a Bcl-2 transgene partially restored CD8αα IELs in Vil-Cre IL-15cKO mice, suggesting that some IL-15 signal other than Bcl-2 is required for maintenance of CD8αα IELs. Furthermore, granzyme B production was reduced, whereas PD-1 expression was increased in CD8αα IELs of Vil-Cre IL-15cKO mice. These results collectively suggested that IEC-derived IL-15 is essential for homeostasis of IELs by promoting their survival and functional maturation.